The Message of Religious Moderation in the Banda Aceh City Murals - Heri Rahmatsyah Putra (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2023)
This study aims to determine the relevance of the mural with the message of religious moderation and the public's perception of the message of religious moderation in the mural as a visual communication medium. The object of this research is a mural in the Peunayong area, Banda Aceh, as a visual communication medium that functions as a medium to convey messages of religious moderation. This research uses a descriptive qualitative approach. Researchers obtained data through primary and secondary sources using observation, interviews, and documentation techniques. The results of the study show the relevance of the murals in Peunayong to the values of religious moderation based on an analysis of visual communication semiotic theory. This study also found that the public's perception of murals as a visual communication medium in conveying moderation in religion was inappropriate based on the mural's position, which needed to be more strategic to get the public's attention.